Effect of Panax notoginseng Saponins and Major Anti-Obesity Components on Weight Loss - Zhang, Xuelian; Zhang, Bin; Zhang, Chenyang; Sun, Guibo; Sun, Xiaobo (Frontiers in Pharmacology, 2021)
The prevalence of individuals who are overweight or obese is rising rapidly globally. Currently, majority of drugs used to treat obesity are ineffective or are accompanied by obvious side effects; hence, the options are very limited. Therefore, it is necessary to find more effective and safer anti-obesity drugs. It has been proven in vivo and in vitro that the active ingredient notoginsenosides isolated from traditional Chinese medicine Panax notoginseng (Burk.) F. H. Chen exhibits anti-obesity effects. Notoginsenosides can treat obesity by reducing lipid synthesis, inhibiting adipogenesis, promoting white adipose tissue browning, increasing energy consumption, and improving insulin sensitivity. Although notoginsenosides are potential drugs for the treatment of obesity, their effects and mechanisms have not been analysed in depth. In this review, the anti-obesity potential and mechanism of action of notoginsenosides were analysed; thus laying emphasis on the timely prevention and treatment of obesity.